COVID-19 and the Stock Market: A Comparative Study of India and the World - Mishra, Nirbhay; Singh, Dharmpal; Jana, Radhakrishna; Kumar Dutta, Sudipta; Majee, Arnab; Ghosh, Debmitra (International Journal of Computer Sciences and Engineering, 2026)
The COVID-19 pandemic had a profound impact on global financial markets, including the stock market in India and worldwide exchanges. This abstract provides an overview of the effects of COVID-19 on these markets and the factors influencing their performance. The outbreak of COVID-19 in early 2020 caused disruptions across various sectors, resulting in significant volatility in stock markets worldwide. In India, benchmark indices such as BSE Sensex and NSE Nifty experienced sharp declines as investors reacted to the uncertainties and potential economic consequences of the virus. The Indian government's strict lockdown measures further contributed to market turmoil, as businesses faced challenges in maintaining operations and generating revenue. Government interventions and monetary stimulus measures aimed at mitigating the economic impact of the crisis provided some stability to the Indian stock market as the pandemic progressed. Sectors like healthcare, pharmaceuticals, and information technology showed relative resilience and even growth due to increased demand and digitalization trends. Conversely, sectors such as travel, hospitality, and retail faced significant setbacks, leading to declines in their stock prices. Similarly, global stock markets witnessed a similar pattern during the pandemic. The initial onset of the crisis led to widespread sell-offs, resulting in substantial declines in major indices such as the Dow Jones Industrial Average, S&P 500, and FTSE 100. However, governments and central banks worldwide implemented unprecedented fiscal and monetary measures, gradually helping stock markets recover. Stimulus packages, low interest rates, and liquidity injections boosted investor confidence and provided support for equities. The pace of economic recovery and the success of vaccination campaigns played crucial roles in shaping stock market performance, both in India and globally. Positive developments regarding vaccine approvals and declining infection rates often resulted in market rallies, while setbacks in virus containment or the emergence of new variants led to increased market volatility. It is worth noting that the impact of COVID-19 on stock markets varied across sectors and companies. Industries that adapted well to the pandemic and capitalized on digital infrastructure experienced growth, while others struggled to survive.